Coleridge and textual instability : the multiple versions of the major poems - Stillinger, Jack (Oxford University Press, 1994)
Jack Stillinger establishes and documents the existence of numerous different authoritative versions of Coleridge's best-known poems: sixteen or more of The Eolian Harp, for example, eighteen of The Rime of the Ancient Mariner, and comparable numbers for This Lime-Tree Bower, Frost at Midnight, Kubla Khan, Christabel, and Dejection: An Ode. Such multiplicity of versions raises interesting theoretical and practical questions about the constitution of the Coleridge canon, the ontological identity of any specific work in the canon, the editorial treatment of Coleridge's works, and the ways in whi.